Assessment of HIV 1 GP120/CD4 Binding Inhibition Potential of Methanolic Extracts of Achyranthes Aspera Leaves - Umaru, Isaac John; Akafa, Tensaba Andes; Akem, Ingwu Joseph; Ngbede, Ocheifa Mathew; Oteng, Joseph; Utioukpan, Ashaka Fidelis; Mijinyawa, Aboki Nwunuji; Akam, Odok Endurance; Ekup, Ogholo Ogholo (African Journal of Medicine, Surgery and Public Health Research, 2025)
Achyranthes aspera (Amaranthaceae) is an important medicinal herb found as a weed throughout Nigeria. Though almost all of its parts are used in traditional systems of medicines, leaves, seeds, roots and shoots are the most important parts which are used medicinally. The present article gives an account of updated information on its phytochemical and pharmacological properties. The Human immunodeficiency virus (HIV) infection is still contributing significantly in morbidities and mortalities in the world today. The drugs normally used to treat the infection are costly, toxic, and less effective due to resistance by HIV. Thus, the assessment of gp120-CD4 binding inhibition potential of Achyranthes aspera leaves extract was conducted using gp120-CD4 capture ELISA kits. Aqueous, methanol, and petroleum ether extracts were prepared at 1000, 500 and 250 μg/ml and tested for gp120-CD4 binding inhibition. Sub-cute toxicity assay was done using albino rats; Biochemical parameters including alanine amino transferase (ALT), aspartate amino transferase (AST) and alkaline phosphatase (ALP) as well as bilirubin for liver and urea, electrolytes and creatinine for kidney functions were evaluated. The results of the effect of crude aqueous, methanol and petroleum ether Achyranthes aspera leaves extract against gp120-CD4 showed inhibition ranging from 1.4 – 17.2 %. with 1000 μg/ml showing highest percentage of inhibition. There was no significant difference (P = 0.862) in terms of percentage inhibition between the three concentrations tested. Methanol extract demonstrated the highest percentage inhibition of gp120-CD4 bindings (17.2 %). No significant difference (P = 0.124) between the three extracts against gp-120-CD4 bindings was observed. The results of the sub-acute toxicity study have shown that, there were no physical changes in animals treated with 500 mg/kg of all the extracts. The result of liver function test revealed that, ALT, AST and ALP were within the normal range (12U/L) for both the high and low concentrations of the extracts including the control. Also result for total protein, albumin, globulin for the test albino rats and that of the control rat were found to be within the normal range 5.1-6.1, 4.2-5.3, and 3.1-3.8 g/dl respectively. For serum electrolyte level, sodium and potassium ions for the various concentrations of the extracts tested and control were also found to be within normal range. The result of kidney function test revealed that, urea, creatinine and direct and total bilirubin of the rats tested and control were all found to be within normal range. In conclusion, ether Achyranthes aspera leaves extract possessed some levels of HIV-1 gp120-CD4 binding inhibition potentials and the extracts was found to be non-toxic at 250 and 500mg/ kg body weight. It can be recommended that, the bioactive compounds should therefore be isolated and tested for gp120-CD4 binding inhibition activity.